2017
DOI: 10.21276/apalm.1245
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma: Clinico-hematological profile in a tertiary care hospital: a three years study

Abstract: Background: To analyze the clinical findings and haematological profile of multiple myeloma patients. Material and methods:All newly diagnosed patients of multiple myeloma between January' 2013 to December' 2015 in the department of pathology, Indira Gandhi Medical College, Shimla were the study subjects. The history and clinical findings were recorded. All relevant blood, radiological investigations including peripheral smears, bone marrow aspiration and biopsy were done.Results: Fifty one patients were diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
4
1
0
Order By: Relevance
“…But Chowdhury et al 20 Table II: Clinical features of multiple myeloma subjects most common physical findings in this study. In the study of Kaushik et al 21 pallor was seen in 94% of the patients which is similar to this study. But it was 44.2% patients in the study of Sultan et al 18 Bone tenderness was in 47% cases observed by Kaushik et al 21 It was lower than the findings in this study possibly due to late stage of presentation in our study.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…But Chowdhury et al 20 Table II: Clinical features of multiple myeloma subjects most common physical findings in this study. In the study of Kaushik et al 21 pallor was seen in 94% of the patients which is similar to this study. But it was 44.2% patients in the study of Sultan et al 18 Bone tenderness was in 47% cases observed by Kaushik et al 21 It was lower than the findings in this study possibly due to late stage of presentation in our study.…”
Section: Resultssupporting
confidence: 91%
“…This is consistent with some other studies in the literature. 1,21,24 In our study compression fracture was observed in 21.88% of the patients, which is similar to Kyle et al 1 (22%) study. In our study osteoporosis was found in 12.5% cases.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Bone lesions visualized on a conventional radiograph, which may include osteolytic lesions or the presence of fractures, are described in 80% of patients at the time of diagnosis. A record similar to that found in this study (74%), where injuries also predominated osteolytic 26 .…”
Section: Methodssupporting
confidence: 91%